2022
DOI: 10.1002/ijfe.2624
|View full text |Cite
|
Sign up to set email alerts
|

Is there J‐curve effect in the US Service Trade? Evidence from asymmetric analysis

Abstract: The J‐curve hypothesis asserts that a depreciation could worsen the trade balance in the short run but improves it in the long run. In testing the hypothesis, almost all previous studies used trade data in goods only. We add to this literature by considering the US trade in insurance and financial services with each of its nine trading partners. Using quarterly data over the period 2003Q1–2019Q4, when we estimated a linear model, we found limited support for the J‐curve effect. However, when we estimated a non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 34 publications
(58 reference statements)
1
12
0
Order By: Relevance
“…We apply the Wald tests ( W S R and W L R ) in short-run and long-run asymmetry for real exchange rate by testing and (Bahmani-Oskooee et al. 2019 ; Bahmani-Oskooee and Karamelikli 2022 ; Ongan et al. 2023 ).…”
Section: Empirical Model and Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…We apply the Wald tests ( W S R and W L R ) in short-run and long-run asymmetry for real exchange rate by testing and (Bahmani-Oskooee et al. 2019 ; Bahmani-Oskooee and Karamelikli 2022 ; Ongan et al. 2023 ).…”
Section: Empirical Model and Methodologymentioning
confidence: 99%
“…If the coefficient of the real exchange rate ( POS and/or NEG ) is positive or insignificant in the short run but negative and significant in the long run, this will imply the asymmetric inverse J Curve (Bahmani-Oskooee et al. 2022 ; Bahmani-Oskooee and Nouira 2021 ; Bahmani-Oskooee and Karamelikli 2022 ).…”
Section: Empirical Model and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Brynjolfsson et al [24] claim (in terms of regression models) that, as a function of intangible investments, the Productivity and Output of General Purpose Technologies (e.g., Artificial Intelligence) show the Productivity-J-Curve. Bao and Le [25] studying the exchange rate between Vietnam and the EU and by Bahmani-Oskooee and Karamelikli [26] in the service trade in the US recently established the existence of a J-Curve in trade relations between countries. The effect of the COVID-19 pandemic on the exchange rate between China and the US, as well as the EU, has also been shown to exhibit a J-Curve [27].…”
Section: Theoretical Aspects and Mathematicalmentioning
confidence: 99%
“…Bahmani-Oskooee and Fariditavana ( 2020 ) used the linear and nonlinear ARDL models and found evidence supporting this hypothesis for different non-food products coded 099 (food preparations, n.e.s.). Bahmani-Oskooee and Karamelikli ( 2022 ) used the linear and nonlinear ARDL models and found evidence supporting asymmetric inverse J-curve for the finance industry with Canada. Both groups of studies found mixed results regarding the validity of the J-curve (Bahmani-Oskooee and Ratha 2004 ).…”
Section: Introductionmentioning
confidence: 99%